1) х = 2,8 ± 0,05; у = 3,5 ± 0,05⇒х +у = 6,3 ± 0,1 ≈ 6,3;х -у = -0,7 ± 0,1≈ -0,7
2) х = 7,9 ± 0,05; у = 3,4 ± 0,05⇒х +у = 11,3 ± 0,1 ≈ 11,3;х -у = 4,5 ± 0,1≈4,5
3) х = 56,31 ± 0,005; у = 17,29 ± 0,005 ⇒х +у = 73,6 ± 0,01 ≈ 73,6;х -у = 39,02 ± 0,01 ≈ 39,02
4) х = 39,23 ± 0,005;у = 26,47 ± 0,005⇒х +у = 65,7 ± 0,01 ≈ 65,70;х -у = 12,76 ± 0,01 ≈ 12,76
5) х = 7,25 ± 0,005; у = 2,9 ± 0,05⇒х +у = 10,15 ± 0,055 ≈ 10,1;х -у = 4,35 ± 0,055 ≈ 4,3
6) х = 5,645 ± 0,005; у = 3,8 ± 0,05⇒х +у = 9,44 ± 0,055 ≈ 9,4;х -у = 1,84 ± 0,055 ≈ 1,8
Объяснение:
(x-4)(7y+3) - (x-4)(5y-9)=(x-4)(7y+3 - 5y+9)=(x-4)(2y+12)
4x-4y+cx - cy=4(x-y) +c(x-y)=(x-y)(4+c)
3a² - ab+2a - 3ac+bc - 2c=a(3a-b+2) - c(3a-b+2)=(a-c)(3a-b+2)